Le dialogue du Panathénaïque d’Isocrate, une dialectique du maître et du disciple ? - Pierre Pontier (Cahiers des Études Anciennes)
The Panathenaicus is unique in the Isocratic corpus in that it includes a real dialogue at the end of the speech. This dialogue allows Isocrates to present himself as a teacher in a discussion of one of his own works. This pedagogical reflection on dialogue is developed in the works that precede the Panathenaicus as well as in the numerous criticisms of eristics. In the final dialogue, Isocrates first distances himself as a teacher from Socratic dialectics and other dialogue-based teaching methods. In an original re-reading of the Delphic maxim "know yourself", he shows the dangers of these types of dialogue for the state of mind of the participants, who can be drawn into the discussion to the detriment of their own equilibrium, including the teacher. On the other hand, the master's speech as it is being written, which is the source of the discussion, provides a framework for it, preserving the pedagogical hierarchy of master and disciple, while helping the latter to progress in his art of speaking and in his social behaviour, in an ideal of moderation.